Pedagogical Conditions of Formation of Moral Feelings in Children of Senior Preschool and Primary School Age - Basyuk, Natalia; Ternopilska, Valentina (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article objectifies the problem of formation of moral feelings in children of senior preschool and primary school age. The author's definition of the concept of moral feelings is offered “moral feelings of children of senior preschool and primary school age we consider to be emotional attitudes to the behavior of others and to their own, which reflect social morality, moral traditions, the real attitude of people to each other”. The main types of moral feelings that should be formed in children at the stage of senior preschool and primary school age are outlined. These include feelings of truth, trust, justice, empathy, kindness, commitment, dignity, friendship and camaraderie, fear, shame, guilt, conscience, altruism, responsibility, duty, success (failure), and civic feelings. Theoretical analysis of scientific and pedagogical literature showed that at the present stage of development of Ukrainian society scientists have paid insufficient attention to the development of theoretical and experimental model of moral feelings of preschoolers and primary school students, did not study the pedagogical conditions of their formation. The article highlights theoretical substantiation and development of pedagogical conditions for the formation of moral feelings in older preschool children. Here the researchers mean deepening and expanding children's knowledge and ideas about moral and ethical categories and their characteristics; emotional saturation of the content of tasks aimed at stimulating the manifestations of children's moral feelings in interaction with the social environment; acquisition by children of moral experience by involvement in various kinds of activity (game, educational-cognitive, pictorial, communicative, estimation-orientation, charitable, socially useful); maintaining a positive emotional state of each child; systematic diagnosis and correction of negative experiences. Various forms and methods were used for their implementation: reading and discussion of fiction and fairy tales, staging, puppet theatrical performances, fairy-tale game technologies and psychological technologies, ethical conversations, moral choice situations, building classes on the methodology of "philosophy for children", ethical training, various games, exercises, project and volunteer activities. Among the pedagogical conditions for the formation of moral feelings of junior students are identified: sufficient comprehension of moral knowledge, norms and rules of conduct by children of primary school age; development of the emotional sphere as a basis for the inclusion of students in educational and cognitive and diverse extracurricular activities, which is based on the principles of personality-oriented approach; gradual process of education of moral feelings of moral schoolchildren with systematic diagnosis and correction of negative experience. Their implementation is ensured by the propaedeutic course "Steps to Responsibility" and the club of extracurricular reading of children's works "Grammar of Morality".